Managerial economics : analysis, problems, cases - Truett, Lila Jean. (South-Western College, 2001)
This book is divided into five parts: The firm and its environment; Production, cost, and profit maximization; Markets and the behavior of the firm; Analysis of project decisions; The firm and the public sector.